TLH versus TAH: a 2 year retrospective comparative study - Dogra, Anju; Kumar, Vinay; Bhushan, Nishu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparoscopic hysterectomy has become a widely accepted technique worldwide, since its introduction by Reich in 1989. The aim of the study was to compare the surgical results and intra- operative and post-operative complications between total laparoscopic hysterectomy (TLH) and total abdominal hysterectomy (TAH). Methods: Authors conducted a retrospective study at SMGS hospital, GMC Jammu between October 2016 to September 2018, 126 patients who underwent TLH and 126 patients who underwent TAH, were included. Results: Authors observed that there was no significant difference between the two groups in respect to patient’s age, parity and indication of surgery. Duration of surgery was found to be longer in TLH than TAH. The length of hospital stay was less in TLH than TAH. Hb drop was more in TAH group. 25 patients of TAH were given post op blood transfusion but only 9 patients of TLH were given post op blood transfusion. The time to ambulation in patients of TLH was much shorter than TAH. Wound infection was more common in TAH as compared to TLH, 5 patients had wound infection and in 4 patients resuturing was done for wound dehiscence. In 8 patients laparoscopy was converted to laparotomy because of adhesions, vascular injury and in one case because of bowel injury. Conclusions: This study showed that TLH can be safely performed by the experienced surgeon as an alternative to abdominal hysterectomy. It offers several benefits over TAH such as smaller incision, earlier ambulation, shorter hospital stay, faster recovery time and does not increase more serious complications than TAH.